Insulin‐like growth factor II‐producing colonic carcinoma presenting with non‐islet cell tumor hypoglycemia: An autopsy report revealing neuroendocrine differentiation in the metastatic foci and literature review. Issue 3 (28th January 2022) - Kondo, Shiori; Hashimoto, Hirotsugu; Nakajima, Kentaro; Miura, Sakiko; Sakuma, Jun; Fukuda, Izumi; Noie, Tamaki; Morikawa, Teppei
Abstract: Non‐islet cell tumor hypoglycemia (NICTH) is a very rare symptom of severe hypoglycemia associated with extrapancreatic tumors. It is considered to be caused by insulin‐like growth factor (IGF)‐II. There have been no autopsy cases of colorectal carcinoma with NICTH confirmed with both serum high molecular weight and tumoral IGF‐II. We report the case of a 46‐year‐old woman with advanced sigmoid colon cancer and liver metastases. She underwent open sigmoidectomy, and histologically, the lesion was a differentiated‐type tubular adenocarcinoma. Postoperative chemotherapy was initiated. However, she experienced repeated hypoglycemia attacks 10 months after the operation, while the liver metastases increased. We examined the cause of hypoglycemia, and finally diagnosed her with NICTH associated with high molecular weight IGF‐II production, which was proven by Western immunoblot of the serum. She died 12 months after surgery and was examined by autopsy. Liver metastases showed a transition from adenocarcinoma to carcinoma with neuroendocrine differentiation. Immunohistochemistry showed that both metastatic carcinoma of the liver and primary colonic adenocarcinoma were positive for IGF‐II. Neuroendocrine differentiation in liver metastases proven by an autopsy may have contributed to tumor growth, which may have exacerbated the symptoms.